FcγR2B B2.4 haplotype predicts increased risk of red blood cell alloimmunization in sickle cell disease patients. Issue 7 (4th May 2020) - Costa Neto, Abel; Santos, Flávia; Ribeiro, Ingrid; Oliveira, Valeria; Dezan, Marcia; Kashima, Simone; Covas, Dimas; Pereira, Alexandre; Fonseca, Guilherme; Moreira, Frederico; Krieger, José; Gualandro, Sandra; et al.
Abstract : BACKGROUND: Red blood cell (RBC) alloimmunization is an important transfusion complication which is prevalent among sickle cell disease (SCD) patients. Autoimmune diseases are a known risk factor for RBC alloimmunization, suggesting that autoimmunity and post‐transfusion alloantibody development occur through similar physiopathological pathways. Polymorphisms in the FcγR2B gene have already been associated with several autoimmune disorders and hypothetically could be associated with RBC alloimmunization. Our goal was to evaluate if important polymorphisms of FcγR2B have an impact on the risk of RBC alloimmunization among SCD patients . STUDY DESIGN AND METHODS: This was a case–control study in which alloimmunized and non‐alloimmunized SCD patients were compared in terms of the genotype frequency of the FcγR2B polymorphisms ‐386G/C, ‐120 T/A, and 695C/T, genotyped through direct Sanger sequencing. RESULTS: A total of 237 patients met the eligibility criteria, 120 cases (alloimmunized) and 117 controls (non‐alloimmunized). RBC alloimmunization was associated with female sex (p < 0.001), lifetime number of RBC units transfused (p = 0.002) and 120 T/A FcγR2B genotype (p = 0.031). The FcγR2B promoter region haplotype 2B.4 (386C120A) was positively associated with RBC alloimunization (p = 0.045). The logistic regression (LR) model identified female sex (OR 10.03, CI 95% 5.16‐19.49; p < 0.001) and FcγR2B 2B.4 haplotype (OR 4.55, CI95% 1.1118.65; p = 0.035) as independent predictors of RBC alloimmunization in SCD patients. CONCLUSION: SCD patients with the FcγR2B 2B.4 haplotype had over a fourfold higher risk for RBC alloimmunization. This highlights the role played by FcγR2B on RBC alloimmunization and may be helpful in identifying the immune responders.